Strategic Analysis of Change Management in Complex Infrastructure Projects: A Systematic Literature Review - Putrawan, I Gusti Ngurah; Sapta, I Ketut Setia; Aristana, I Nengah; Putra, Gede Cahyadi; Chandra, Vony Surya; Nikmah, Choirul (IKIP Widya Darma Surabaya, 2025)
Objective: This study systematically reviews strategic change management in complex infrastructure projects involving multiple stakeholders, advanced technologies, and multidimensional risks. Method: Using a Systematic Literature Review (SLR) approach on scientific articles published between 2019 and 2024, this research identifies adaptive strategies applied to address change challenges, including the integration of digital technologies (BIM, IoT, AI), transformational and participative leadership approaches. Results: Findings indicate that digitalisation and sustainability have become the main pillars of modern infrastructure project management, while social aspects such as organisational justice and social procurement are increasingly prioritised. Furthermore, managing project complexity requires a multidisciplinary approach that integrates advanced technologies, adaptive organisational capabilities, and collaborative leadership to minimise resistance to change. Novelty: This study contributes novelty by mapping the literature trends on change management strategies in complex infrastructure projects and offering practical implications for project managers and policymakers in formulating effective and sustainable change strategies in the era of digital transformation and global uncertainty.